2012 Haida Gwaii Quake: Insight Into Cascadia's Subduction Extent. (26th February 2013) - Szeliga, Walter
Abstract : The limits of Cascadia were first defined to contain nearly the entire margin of the Pacific Northwest, from Cape Mendocino through the Alaska Panhandle [ Schuchert, 1910; Schuchert and Barrell, 1914]. Since that time, the boundary of Cascadia has shrunk to become essentially synonymous with the region where the Juan de Fuca plate subducts beneath the North American plate. As a consequence, seismic hazard assessments in the Pacific Northwest have conventionally focused on the potential for large megathrust earthquakes along the interface of the Juan de Fuca and North American plates.